Visual saliency detection in image and video data - Luo, Ye (2014)
The study of psychology and cognitive science has shown that the human perception is selective. When seeing images or watching videos, we mainly focus on a salient sub-region of an image, e.g. the salient object, and follow this salient object in image sequences. Efficient saliency analysis and accurate salient object detection are fundamental problems to various computer vision applications, i.e. image\slash video retargeting, object recognition and etc.